Immune Response toward Mycobacterium Tuberculosis Infection - Ikram Hasanuddin, Abdi Dzul; Roswita, Nanang; Virnanda Amu, Ivan (Green Medical Journal, 2020)
Understanding the human immune response toward Mycobacterium tuberculosis infection is important for controlling its infection. Its transmission through the air consists of "droplets nuclei" containing TB bacilli. After initial infection, the human body will provide diverse immune responses and will determine different clinico-histopathologic finding. This response starts from innate immunity that consists of phagocytosis by distal alveolar macrophages or nasal microfold cells, then will be continued by dendritic cells to be transferred to mediastinal lymph nodes to induced adaptive immune responses. This response is mediated by cells through IFN- Î³ signaling which will enhance phagocytosis. If this response is effective, there will be a latent infection with an initial histopathological finding of caseosa granulomas and predominantly followed by chronic granulomas. In a few cases, it can be reactivated via the IL-10 activation pathway and exogenous factors, it will induce a great adaptive immune reaction and provide more severe clinico-histopathological manifestation. The existence of the human body's immune response to Mycobacterium tuberculosis, etiher innate or adaptive immunity will determine the clinical course and pathology that will occur.